2002
DOI: 10.2188/jea.12.280
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Determinants for Change in Activities of Daily Living: A Cohort Study of the Elderly People in Beijing.

Abstract: To describe changes in activities of daily living (ADL) of community-dwelling Beijing elderly people, observed for 8 years, and to identify the demographic characteristics that predict the functional change. Four sets of interview data from 1992 to 2000 were used to evaluate changes among Beijing elderly aged 55 years and over. Results revealed that prevalence of disability increased from 3.9% to 7.1% during the 8 years of follow-up with the average increasing rate of disability was 0.41% per year. Meanwhile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…The average increase in the disability rate was 0.16% per year in younger frail adults compared with 0.48% a year in older frails. 29 The WHO has pointed out the high prevalence of disabilities among women, people living in poverty, and seniors in developing countries. 30 This is similar to an empirical study in the United States that found increasing age, female gender, and being married strongly predicted difficulties in daily life activities, such as taking medication, grocery shopping, preparing meals and using the telephone.…”
Section: Discussionmentioning
confidence: 99%
“…The average increase in the disability rate was 0.16% per year in younger frail adults compared with 0.48% a year in older frails. 29 The WHO has pointed out the high prevalence of disabilities among women, people living in poverty, and seniors in developing countries. 30 This is similar to an empirical study in the United States that found increasing age, female gender, and being married strongly predicted difficulties in daily life activities, such as taking medication, grocery shopping, preparing meals and using the telephone.…”
Section: Discussionmentioning
confidence: 99%
“…The geographic distribution, economic status, age, and education of the sample represent the older population of Beijing, as obtained from the Fourth National Census Data (27). As described elsewhere (27,28), the cohort was assembled in 1992; the response rate was 91.2%; participants were followed every 2–3 years. At the time of the 1997 survey, 784 subjects (24.1%) had died, and 430 were missing at follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…This dataset was provided by the Beijing Geriatric Clinical and Research Centre, Xuanwu Hospital of Capital Medical University, Beijing, China. Distributions of gender, age groups, and educational categories of the study sample represent those of older population in Beijing, as obtained from the Fourth National Census Data [22]. As described elsewhere [22,23], the cohort was assembled in 1992 (The response rate at baseline was 91.2%), and followed every two to three years (cycles 1, 2, and 3) in 1994, 1997 and 2000.…”
Section: Methodsmentioning
confidence: 99%